Seeking information about health and lifestyle on the Internet - Ágústa Pálsdóttir 1955- (2009)
Introduction. The paper focuses on factors related to purposive health and lifestyle information seeking on the Internet, examining participants' access to the Internet from four access points; the prevalence of their health and lifestyle information seeking, as well as information seeking in relation to other topics; the barriers to information seeking they experienced; and self-evaluation of their skills at seeking online information. Method. The sample consists of 1,000 Icelanders, aged eighteen to eighty, randomly selected from the National Register of Persons in Iceland. The data were gathered as a postal survey during spring 2007. Response rate was 47%. Analysis. Based on the participants' health and lifestyle information seeking in twenty-two sources, k-means cluster analysis was used to draw four clusters: passive, moderately passive, moderately active and active. Results. The active and moderately passive clusters have greater access to the Internet and their members seek online information more frequently than the passive and moderately active clusters. All clusters seek information about health and lifestyle less frequently than information about other topics. The passive and moderately active clusters experience more barriers to information seeking than the other two clusters. However, the passive and moderately passive clusters consider themselves to have more competency at seeking online information than do the moderately passive and active clusters. Conclusions. For the Internet to be used in an effective way for health promotion it is necessary to gain more complete knowledge of the various aspects of health information behaviour and identify the characteristics of those who have adopted it to seek information, compared with those who have done so to a lesser extent.